2017
DOI: 10.1007/s12325-016-0467-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Vedolizumab in Ulcerative Colitis and Crohn’s Disease Patients Stratified by Age

Abstract: IntroductionThe efficacy and safety of vedolizumab, a gut-selective α4β7 integrin antibody, were demonstrated in the GEMINI 1 and GEMINI 2 clinical trials of adults aged 18–80 years. We investigated the efficacy and safety of vedolizumab in patients stratified by age from the GEMINI trials.MethodsSafety and efficacy, including clinical response, clinical remission, and corticosteroid-free remission, at week 6 and/or 52 were determined post hoc in patients aged <35, 35 to <55, and ≥55 years.ResultsAt baseline, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
94
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(97 citation statements)
references
References 29 publications
0
94
0
3
Order By: Relevance
“…In total, 15 studies (13 full‐text articles and two abstracts) met the eligibility criteria and reported the occurrence of infections or malignancies in IBD patients ≥60 years old. Nine were cohort studies, five were case‐control studies and one was the post hoc analysis of a randomised controlled trial (RCT) . All studies reported at least one relevant outcome for IBD patients, and two of them also reported data regarding CD and UC patients, separately.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 15 studies (13 full‐text articles and two abstracts) met the eligibility criteria and reported the occurrence of infections or malignancies in IBD patients ≥60 years old. Nine were cohort studies, five were case‐control studies and one was the post hoc analysis of a randomised controlled trial (RCT) . All studies reported at least one relevant outcome for IBD patients, and two of them also reported data regarding CD and UC patients, separately.…”
Section: Resultsmentioning
confidence: 99%
“…32 This targeted approach is novel in the Japanese context, as the therapies recommended in guidelines for IBD treatment (mesalamine, sulfasalazine, corticosteroids, and immunomodulators) may need to be applied topically via an enema to achieve optimal results. 1,33 In addition, immunomodulators such as 6-mercaptopurine and cyclosporine may be associated with some serious side effects, such as bone marrow suppression, development of nonmelanomatous skin cancers, and hepatosplenic T-cell lymphoma. 1,8 Because vedolizumab has been shown to be effective in patients with moderately to severely active ulcerative colitis previously treated with corticosteroids, purine antimetabolites, and/or TNFα inhibitors, 14 this humanized monoclonal antibody has the potential to provide a new line of therapy for patients with ulcerative colitis that is resistant to treatments currently available in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…A descriptive retrospective analysis of pivotal studies in UC and CD demonstrated that the safety profiles of vedolizumab and placebo were similar in patients aged <35 years, 35 to 55 years, and ≥55 years. (18) Vedolizumab-treated UC and CD patients in the oldest subgroup (n = 147) had fewest serious infections (<1%) and adverse events leading to hospitalization (11%) compared with patients in younger subgroups. Early experience in clinical practice (N = 66 IBD patients aged ≥18 years) has shown that older age may correlate with a higher likelihood of vedolizumab response.…”
Section: Medical Management In Elderly Ibd Patientsmentioning
confidence: 94%
“…Although recent literature has documented the efficacy and safety of IBD treatments in the elderly,(1318) there are substantial gaps in our understanding of the special needs and challenges of this patient population. Most clinical trials have excluded or enrolled insufficient numbers of elderly patients, significantly limiting insights into the safety and efficacy of IBD therapy as a function of age.…”
Section: Introductionmentioning
confidence: 99%